OP0011 A Randomized, Double-Blind, Phase 3 Equivalence TRIAL Comparing the Etanercept Biosimilar, Hd203, with Enbrel®, in Combination with Methotrexate (MTX) in Patients with Rheumatoid Arthritis (RA). (10th June 2014) - Bae, S.-C.; Kim, J.-S.; Choe, J.-Y.; Park, W.; Lee, S.-R.; Ahn, Y.; Seo, Y.
Abstract : Background: Etanercept is a recombinant fusion protein that blocks TNF activity. HD203 is a biosimilar of etanercept. In a double-blind, randomized study in healthy volunteers, HD203 and Enbrel® were comparable with regards to pharmacokinetics, safety and tolerability. Objectives: To evaluate the equivalence in efficacy and to compare the safety of HD203 (biosimilar etanercept) and Enbrel® (reference etanercept), in combination with MTX in patients with RA. (ClinicalTrials.gov identifier NCT01270997 ). Methods: Patients (male or female aged ≥20 years) with active RA were randomly assigned (1:1) to 25 mg HD203 or Enbrel®, administered subcutaneously twice weekly with MTX for 48 weeks. The primary endpoint was the proportion of patients achieving ACR20 at week 24. Secondary endpoints included ACRn, change in DAS28, and EULAR response at week 24 and 48, safety and immunogenicity. Efficacy and safety were evaluated at screening, week 0, 2, 4, 8, 12, 16, 20, and 24. Immunogenicity, efficacy and safety were also evaluated at week 36 and 48. Results: In total, 294 patients were randomized: 147 to HD203 and 147 to Enbrel®. The proportion of patients achieving ACR20 at week 24 (primary endpoint) was not significantly different for HD203 and Enbrel® (Table) and equivalence in efficacy was demonstrated within predefined margins. In addition, there were no statistically significant differences between proportions achieving ACR20 at weeks 12 and 48. Similar trends were seen for ACR50 and ACR70, however the proportion of patients achieving ACR50 at week 24 and 48 was higher with HD203 than with Enbrel®. There were no statistically significant differences between the groups for ACRn, change in DAS28, and EULAR response at week 24 and 48. Analysis of the safety set (HD203, n=147; Enbrel®, n=146) revealed no statistically significant difference in the number of treatment-emergent (all-causality) adverse events (AEs): HD203 76.87% vs. Enbrel® 78.08% (p=0.8040). Furthermore, no statistically significant differences between HD203 and Enbrel® were observed with regards to adverse drug reactions, serious AEs, or discontinuations due to AEs. No unexpected AEs were observed, and few patients tested positive for anti-drug antibodies. Conclusions: The study met the primary endpoint of demonstrating equivalence in efficacy of HD203 compared with Enbrel®. HD203 was well tolerated, with a safety profile comparable to that of Enbrel® in this population of Korean patients with RA. Disclosure of Interest: S.-C. Bae: None declared, J.-S. Kim Grant/research support: Hanwha Chemical, J.-Y. Choe: None declared, W. Park: None declared, S.-R. Lee Employee of: Hanwha Chemical, Y. Ahn Employee of: Hanwha Chemical, Y. Seo Consultant for: Hanwha Chemical DOI: 10.1136/annrheumdis-2014-eular.3558